Running a marathon - its influence on achilles tendon structure - Rabello, L. M.; Albers, I. S.; van Ark, M.; Diercks, R. L.; van den Akker-Scheek, I.; Zwerver, J. (Journal of Athletic Training, 2020)
Context: Several studies have been conducted to better understand the effect of load on the Achilles tendon structure. However, the effect of a high cumulative load consisting of repetitive cyclic movements, such as those that occur during the running of a marathon, on Achilles tendon structure is not yet clear. Clinicians, coaches, and athletes will benefit from knowledge about the effects of a marathon on the structure of the Achilles tendon.